Development of E-Story Book Media Based on Local Wisdom and Ecoliteracy in Reading Comprehension Learning for Students at Ulak Embacang Public Elementary School - Perawati Perawati; Santi Oktarina; Erna Retna; Makmum Raharjo (AL-ISHLAH: Jurnal Pendidikan, 2026)
The limited integration of digital learning media incorporating local wisdom and ecoliteracy in elementary reading instruction motivated this study, which aimed to develop a valid, practical, and effective e-storybook for reading comprehension. This development research employed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study was conducted at SD Negeri Ulak Embacang, a rural elementary school in South Sumatra, involving fourth-grade students in small-group and field testing. Data were collected through observations, interviews, questionnaires, and pretest–posttest assessments, and analyzed using feasibility and practicality percentages alongside N-Gain scores. The developed e-storybook demonstrated high validity based on expert evaluations of content (96.6%), media (95%), and language (93.3%). Practicality testing yielded an average score of 91.55% in the small-group phase, indicating strong usability. Effectiveness results showed a significant improvement in students’ reading comprehension, with an N-Gain score of 0.84 (high category). The findings indicate that the e-storybook is a valid, practical, and effective digital learning medium. Its integration of local wisdom and ecoliteracy provides contextualized learning experiences that enhance comprehension while promoting digital literacy and environmental awareness among elementary students. Consequently, it offers a valuable instructional resource for teachers, particularly in rural educational settings.